Genetic variation in mice affects closed femoral fracture pattern outcomes. Issue 3 (March 2019) - Bartnikowski, Michal; Bartnikowski, Nicole; Woloszyk, Anna; Matthys, Romano; Glatt, Vaida
Highlights: Fracture pattern reproducibility was influenced by the structural and material properties of bone. The structural and material properties of bone should be considered for studies requiring reproducible fracture patterns. A binomial logistic regression confirmed that bone morphometry was the strongest predictor of fracture pattern. A kinetic energy of 20 mJ is more than sufficient to reproducibly create closed transverse fractures in mice. X-ray and μCT measurements were highly correlated, confirming X-rays can be used to accurately calculate bone geometry. Abstract: The purpose of this study was to determine whether differences in structural and material properties of bone between different mouse strains influence the fracture patterns produced under experimental fracture conditions. Femurs of C57BL/6 (B6), C3H/HeJ (C3H), and DBA/2 (DBA) strains were evaluated using micro-computed tomography (μCT), measurements derived from radiographic images and mechanical testing to determine differences in the geometry and mechanical properties. A fracture device was used to create femoral fractures on freshly sacrificed animals using a range of kinetic energies (∼20–80   m J ) which were classified as transverse, oblique, or comminuted. B6 femurs had the lowest bone volume/total volume (BV/TV) and bone mineral density (BMD), thinnest cortex, and had the most variable fracture patterns, with 77.5% transverse, 15% oblique, and 7.5% comminuted fractures. In contrast, C3H had the highest BV/TV, BMD, and thickest cortices, resulting in 97.5% transverse, 2.5% oblique, and 0% comminuted fractures. DBA had an intermediate BV/TV and thickness of cortices, with BMD similar to C3H, resulting in 92.9% transverse, 7.1% oblique, and 0% comminuted fractures. A binomial logistic regression confirmed that bone morphometry was the single strongest predictor of the resulting fracture pattern. This study demonstrated that the reproducibility of closed transverse femoral fractures was most influenced by the structural and material properties of the bone characteristics in each strain, rather than the kinetic energy or body weight of the mice. This was evidenced through geometric analysis of X-ray and μCT data, and further supported by the bone mineral density measurements from each strain, derived from μCT. Furthermore, this study also demonstrated that the use of lower kinetic energies was more than sufficient to reproducibly create transverse fractures, and to avoid severe tissue trauma. The creation of reproducible fracture patterns is important as this often dictates the outcomes of fracture healing, and those studies that do not control this potential variability could lead to a false interpretation of the results.